Agriculture and the WTO : Creating a Trading System for Development - Ingco, Merlinda D.; Nash, John D. (Washington, DC: World Bank and Oxford University Press, 2013)
This publication explores the key issues and options in agricultural trade liberalization from a developing country perspective. Chapters cover market access, domestic support, export competition, quota administration methods, food security, biotechnology, intellectual property rights, agricultural trade under the Uruguay Round Agreement on Agriculture (URAA), and many other subjects, always focusing on the question of how the outcome of the World Trade Organization (WTO) negotiations can be made pro-development. Material is covered in summary and in comprehensive detail with supporting data tables, text boxes, figures, and a detailed table of contents. Many chapters have a substantial bibliography, listings of online resources, and tables summarizing the major points of WTO member country proposals that deal directly with each chapter topic.